Systems of psychotherapy dialectical tensions and integration - Fromme, Donald K. (Springer eBooks., 2011)
Psychotherapy today encompasses a broad spectrum of approaches that focus to a varying extent on psychophysiological, behavioral, environmental, or other aspects of human problems. Despite the overlap that exists between many of these approaches, there is no method that integrates more than a few of these aspects. It is therefore important to understand the inherent advantages and disadvantages of each therapy system, and how each helps people to solve their problems. Systems of Psychotherapy: Dialectical Tensions and Integration provides an in-depth overview of the major therapeutic systems in practice today and outlines the philosophical differences and opportunities for integration among them. This volume also considers the new ideas and approaches to therapy stemming from the postmodernist and integrative movements. By highlighting the unique merits of each system, readers are encouraged to combine factors present in the various systems to create a comprehensive view of human nature and functioning that will improve therapeutic outcomes. Topics covered in this volume include: Empirical foundations of psychotherapy Treatment planning and the initial interview. Psychopharmacology. Cognitive-Behavioral interventions. Humanistic approaches. Interpersonal approaches. Family systems and couples approaches. Ecosystemic interventions Systems of Psychotherapy is an educational text which spans historical and contemporary issues in psychotherapy and is an ideal reference for students of clinical, counseling, and school psychology, psychiatric residents, and graduate students in clinical social work.